High prostate cancer gene 3 (PCA3) scores are associated with elevated Prostate Imaging Reporting and Data System (PI‐RADS) grade and biopsy Gleason score, at magnetic resonance imaging/ultrasonography fusion software‐based targeted prostate biopsy after a previous negative standard biopsy. (24th May 2016) - De Luca, Stefano; Passera, Roberto; Cattaneo, Giovanni; Manfredi, Matteo; Mele, Fabrizio; Fiori, Cristian; Bollito, Enrico; Cirillo, Stefano; Porpiglia, Francesco
Abstract : Objective: To determine the association among prostate cancer gene 3 (PCA3) score, Prostate Imaging Reporting and Data System (PI‐RADS) grade and Gleason score, in a cohort of patients with elevated prostate‐specific antigen (PSA), undergoing magnetic resonance imaging/ultrasonography fusion software‐based targeted prostate biopsy (TBx) after a previous negative randomised 'standard' biopsy (SBx). Patients and Methods: In all, 282 patients who underwent TBx after previous negative SBx and a PCA3 urine assay, were enrolled. The associations between PCA3 score/PI‐RADS and PCA3 score/Gleason score were investigated by K‐means clustering, a receiver operating characteristic analysis and binary logistic regression. Results: The PCA3 score difference for the negative vs positive TBx cohorts was highly statistically significant. A 1‐unit increase in the PCA3 score was associated to a 2.4% increased risk of having a positive TBx result. A PCA3 score of >80 and a PI‐RADS grade of ≥4 were independent predictors of a positive TBx. The association between the PCA3 score and PI‐RADS grade was statistically significant (the median PCA3 score for PI‐RADS grade groups 3, 4, and 5 was 58, 104, and 146, respectively; P = 0.006). A similar pattern was detected for the relationship between the PCA3 score and Gleason score; an increasing PCA3 score was associated with a worsening Gleason score (median PCA3 score equal to 62, 105, 132, 153, 203, and 322 for Gleason Score 3+4, 4+3, 4+4, 4+5, 5+4, and 5+5, respectively; P < 0.001). Conclusion: TBx improved PCA3 score diagnostic and prognostic performance for prostate cancer. The PCA3 score was directly associated both with biopsy Gleason score and PI‐RADS grade: notably, in the 'indeterminate' PI‐RADS grade 3 subgroup.